A Multi‐Mitochondrial Anticancer Agent that Selectively Kills Cancer Cells and Overcomes Drug Resistance. (18th January 2017) - Peng, Yong Bo; Zhao, Zi Long; Liu, Teng; Xie, Guo Jian; Jin, Cheng; Deng, Tang Gang; Sun, Yang; Li, Xiong; Hu, Xiao Xiao; Zhang, Xiao Bing; Ye, Mao; Tan, Wei Hong
Abstract: Mitochondria are double‐membrane‐bound organelles involved mainly in supplying cellular energy, but also play roles in signaling, cell differentiation, and cell death. Mitochondria are implicated in carcinogenesis, and therefore dozens of lethal signal transduction pathways converge on these organelles. Accordingly, mitochondria provide an alternative target for cancer management. In this study, F16, a drug that targets mitochondria, and chlorambucil (CBL), which is indicated for the treatment of selected human neoplastic diseases, were covalently linked, resulting in the synthesis of a multi‐mitochondrial anticancer agent, FCBL. FCBL can associate with human serum albumin (HSA) to form an HSA–FCBL nanodrug, which selectively recognizes cancer cells, but not normal cells. Systematic investigations show that FCBL partially accumulates in cancer cell mitochondria to depolarize mitochondrial membrane potential (MMP), increase reactive oxygen species (ROS), and attack mitochondrial DNA (mtDNA). With this synergistic effect on multiple mitochondrial components, the nanodrug can effectively kill cancer cells and overcome multiple drug resistance. Furthermore, based on its therapeutic window, HSA–FCBL exhibits clinically significant differential cytotoxicity between normal and malignant cells. Finally, while drug dosage and drug resistance typically limit first‐line mono‐chemotherapy, HSA–FCBL, with its ability to compromise mitochondrial membrane integrity and damage mtDNA, is expected to overcome those limitations to become an ideal candidate for the treatment of neoplastic disease. Abstract : Power outage for cancer : A drug that targets mitochondria, F16, and chlorambucil (CBL) were covalently linked, resulting in the formation of a multi‐mitochondrial anticancer agent, FCBL. FCBL can associate with human serum albumin (HSA) to form an HSA–FCBL nanodrug, which selectively recognizes cancer cells, leaving normal cells alone. Systematic investigations show that FCBL partially accumulates in cancer cell mitochondria to depolarize mitochondrial membrane potential, increase reactive oxygen species, and attack mtDNA. The nanodrug can effectively kill cancer cells and overcome multidrug resistance.